ATMOSPHERIC METHANE AND GLOBAL CHANGE - Wuebbles D.J.; Hayhoe K. (My University, 2002)
Methane (CH4) is the most abundant organic trace gas in the atmosphere. In the distant past, variations in natural sources of methane were responsible for trends in atmospheric methane levels recorded in ice cores. Since the 1700s, rapidly growing human activities, particularly in the areas of agriculture, fossil fuel use, and waste disposal, have more than doubled methane emissions. Atmospheric methane concentrations have increased by a factor of 2–3 in response to this increase, and continue to rise. These increasing concentrations have raised concern due to their potential effects on atmospheric chemistry and climate. Methane is important to both tropospheric and stratospheric chemistry, significantly affecting levels of ozone, water vapor, the hydroxyl radical, and numerous other compounds. In addition, methane is currently the second most important greenhouse gas emitted from human activities. On a per molecule basis, it is much more effective a greenhouse gas than additional CO2. In this review, we examine past trends in the concentration of methane in the atmosphere, the sources and sinks that determine its growth rate, and the factors that will affect its growth rate in the future. We also present current understanding of the effects of methane on atmospheric chemistry, and examine the direct and indirect impacts of atmospheric methane on climate.